Analysis of the Effect of Sales and Customer Satisfaction at Cafe Tentador on the Marketing Strategy Optimization Using Fuzzy Logic - Nurlindasari Tamsir; Vivi Rosida; Widyawati Widyawati; St. Amina H. Umar (PROtek : Jurnal Ilmiah Teknik Elektro, 2026)
Business competition in the culinary industry is becoming progressively intense, particularly in strategic areas such as Pangkajene District, Pangkajene dan Kepulauan Regency. One of the cafés operating in this region is Cafe Tentador. The sales performance of the café demonstrated fluctuation from 2020 to 2023 due to various factors, including the Covid-19 pandemic. In addition to sales performance, customer satisfaction is a crucial factor in maintaining business competitiveness. Therefore, this study aims to analyze the effect of sales and customer satisfaction on the marketing strategy optimization at Cafe Tentador using the Fuzzy Logic method. The analysis, conducted using the Mamdani Fuzzy Logic approach to evaluate the effectiveness of marketing strategies by considering sales and customer satisfaction factors, reveals that the current marketing strategy is at a moderate (fairly good) level. This indicates that while the existing strategy provides a positive effect on the company's performance, there is still a room for improvement and increased effectiveness. Recommended insights include enhancing customer satisfaction through satisfaction surveys, loyalty programs, and responsive feedback, as well as boosting sales through attractive promotions, collaborations with influencers, and menu development.